SAT0071 Assessment of Rheumatoid Arthritis Disease Activity by Patients and Physicians: do Physicians Detect Improvement before the Patient Does?. (10th June 2014) - Bensen, W.G.; Thorne, C.; Baer, P.; Chow, A.; Arendse, R.; Baker, M.; Haraoui, B.; Jovaisas, A.; Sampalis, J.S.; Rampakakis, E.; Lehman, A.J.; Nantel, F.; et al.
Abstract : Objectives: Patient (PtGA) and physician (MDGA) global assessment of disease activity measure the same construct from two different perspectives. The objective of this study was to assess the agreement between these two measures over time as ascertained in Canadian routine clinical practice in patients with RA treated with infliximab or golimumab. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with infliximab or golimumab as first biologics or after having been treated with a biologic for less than six months. In this analysis, people with RA treated with infliximab who were enrolled between 2002 and 2012 and had at least one follow-up assessment and up to 60 months of follow up were included. PtGA and MDGA were measured on a 10-point Numerical rating scale (NRS) and 10 cm visual analog scale (VAS), respectively. The association between treatment duration and difference between MDGA and PtGA was assessed with linear regression. Internal consistency was assessed with the intra-class correlation coefficient (ICC) and Cronbach's alpha (CA). Results: A total of 675 patients assessed over 4193 visits during a mean follow up time of 20 months were included in the analyses. The overall mean (SD) PtGA and MDGA was 3.73 (2.89) and 3.38 (2.67), respectively (P<0.001). At baseline the mean difference between the MDGA and PtGA was +0.41 (P<0.001). However, during all the follow up assessments, this was reversed, with PtGA being significantly higher (worse) when compared to MDGA. The mean difference changed by -0.012 per month (P<0.001) indicating progressively higher scores by patients over time compared to physicians. The overall ICC and CA were 0.767 and 0.770, respectively, indicating moderate agreement. Both ICC and CA decreased over time. The mean difference between MDGA and PtGA assessments was non-significantly higher for females (-0.37) when compared to males (-0.29) and significantly higher for patients with history of MTX use (-0.43 vs. -0.18; P=0.002). TJC, SJC, CDAI and SDAI had positive and significant (P<0.001) associations with increased difference between MDGA and PtGA. Slope analysis showed that MD assessments declined by -0.265/month and Pt assessments declined by -0.189/month (P<0.001). Conclusions: The results of this Canadian longitudinal observational registry have shown that there is poor agreement between physician-based and patient-based assessments of disease activity. In addition, the rate of reduction in disease activity over time is considerably higher when rated by physicians when compared to patients. In this chronic condition, physicians should be aware of this increasing discordance between the patient and physician global when making treatment decisions and managing patient expectations over time. Acknowledgements: We thank Dr. Mary Bell, Sunnybrook Health Sciences Centre, for her contribution to the development of this analysis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3902